Metzler Lexikon Avantgarde 2009
DOI: 10.1007/978-3-476-05202-5_14
|View full text |Cite
|
Sign up to set email alerts
|

M

Abstract: A rapid and economical method for hybrid purity testing of tomato (Lycopersicon esculentum L.) F 1 hybrids using ultrathin-layer isoelectric focusing of alcohol dehydrogenase variants from seedsIn the cultivated tomato (Lycopersicon esculenturn L.), two electrophoretic variants of the enzyme alcohol dehydrogenase (ADH) encoded by the alleles Adh-I and Adh-1' are found. A rapid and economic method for testing the hybrid purity of tomato F 1 seeds, based on the expected presence of Adh-1 alleles, was developed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 3 publications
0
32
0
2
Order By: Relevance
“…Only PCB 105 has been assigned a TEF by the WHO, and so this is the only one of the three congeners to be reported here. (8) Rudel et al found PCB 105 above their limit of detection (LOD) (∼0.2 micrograms per gram of house dust or 200,000 ppt) in 9 (7.6%) of the 119 homes. The median LOD for PCB 105 in the present study was 2.1 ppt.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Only PCB 105 has been assigned a TEF by the WHO, and so this is the only one of the three congeners to be reported here. (8) Rudel et al found PCB 105 above their limit of detection (LOD) (∼0.2 micrograms per gram of house dust or 200,000 ppt) in 9 (7.6%) of the 119 homes. The median LOD for PCB 105 in the present study was 2.1 ppt.…”
Section: Discussionmentioning
confidence: 98%
“…Note that this investigation was initiated in mid-2005, and the determination of outlier status was based on calculation of the TEQs using the 1998 TEFs, but all TEQ results shown here have been recalculated using the 2005 TEFs. (7,8) Twenty house dust results (2.6%) met the statistical criterion to be classified as outliers (see Table II and online supplemental Table II for listing of dust outlier results). If the 2005 TEFs had been used instead of the 1998 TEFs, 15 of the 20 original cases would have met the criterion for being classified as an outlier (i.e., a TEQ more than 2.5 SD above the mean of the logtransformed data), but no new cases met the criterion.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, the rate of COD hydrogenation in Rh(MonoPhos) 2 (COD)BF 4 was determined as 0.071 min -1 , which is somewhat slower than the corresponding DuPhos complex [20]. In a recent study, the rate of COD hydrogenation in Rh(MonoPhos) 2 (COD)BF 4 was determined as 0.071 min -1 , which is somewhat slower than the corresponding DuPhos complex [20].…”
Section: Induction Period Caused By Slow Hydrogenation Of Cod or Nbdmentioning
confidence: 97%
“…On the other hand, measurements of the reactive copper concentration may be relevant as it is probably related to that fraction of copper which is available to aquatic organisms [20]. However, the reactive fraction should not be equated with the free or inorganic copper fraction as 99% of the copper is known to be organically complexed in these waters [21].…”
Section: Determination Of Electrochemically Labile Copper In Natural mentioning
confidence: 99%